Liquid-liquid mass transfer in microfluidic reactors: Assumptions and realities of non-ideal systems - van Stee, Joren; Adriaenssens, Pieter; Kuhn, Simon; Binnemans, Koen; Van Gerven, Tom (Chemical engineering science, 2022)
•Cobalt(II) was extracted with an undiluted ionic liquid in a microfluidic reactor.•The system is subject to several non-idealities (e.g., non-linear equilibrium).•The effect of said non-idealities on the mass transfer coefficient are estimated.•Gas–liquid like behavior occurs depending on the continuous phase viscosity. The mass transfer coefficient, kLα, is often used to benchmark the liquid–liquid mass transfer performance in a microfluidic reactors. Cobalt(II) was extracted with an undiluted, highly viscous, ionic liquid from an aqueous phase in a microfluidic reactor (1 mm ID) and kLα values were determined (0.0002–0.033 s−1). It is concluded that the high viscosity of the ionic liquid causes two-phase slip, greatly reducing the efficiency of the microfluidic reactor. Furthermore, deviations (or non-idealities) from the assumptions related to mass transfer calculations (e.g., no reaction effects) can have a drastic impact on the measured kLα values. This work reports deviations between −25 and +40%. In general, it is shown how several non-idealities (i.e., a high continuous phase viscosity, non-linear equilibrium behavior and concentration effects) can affect the calculated mass transfer coefficient.